Efektivitas manajemen risiko operasional pada bank syariah: studi terhadap sistem kepatuhan dan teknologi informasi - Agusty, rizal ubaidilbar (Maliki Interdisciplinary Journal, 2025)
Operational risk management is a fundamental aspect in ensuring the stability and credibility of Islamic banks. This type of risk encompasses system failures, human errors, and non-compliance with Sharia principles and regulatory standards. This article aims to analyze the effectiveness of operational risk management in Islamic banks located in East Java, focusing on two key elements: compliance systems and information technology. The study employs a conceptual approach and literature review based on scholarly journals, regulatory policies, and relevant academic sources. Findings indicate that compliance systems play a vital role in safeguarding Sharia integrity and maintaining sound operational governance. Meanwhile, information technology enables risk mitigation processes to be automated, accurate, and real-time. Nonetheless, challenges persist, including limited digital integration, insufficient technological literacy among human resources, and high infrastructure investment needs. Therefore, it is essential to strengthen human resource capacity, invest in Sharia-compliant digital infrastructure, and promote management commitment to compliance and digital transformation. This study offers a conceptual contribution to the development of more adaptive and relevant risk management strategies for Islamic banking in the digital era.